Motor Neuron Diseases and Neuroprotective Peptides: A Closer Look to Neurons - Zuccaro, Emanuela; Piol, Diana; Basso, Manuela; Pennuto, Maria (Frontiers in Aging Neuroscience, 2021)
Motor neurons (MNs) are specialized neurons responsible for muscle contraction that specifically degenerate in motor neuron disorders, such as amyotrophic lateral sclerosis (ALS), spinal and bulbar muscular atrophy (SBMA), and spinal muscular atrophy (SMA). Distinct classes of MNs degenerate at different rates in disease, with a particular class named fast-fatigable MNs (FF-MNs) degenerating first. The etiology behind the selective vulnerability of FF-MNs is still largely under investigation. Among the different strategies to target MNs, the administration of protective neuropeptides is one of the potential therapeutic interventions. Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuropeptide with beneficial effects in many neurodegenerative diseases, including Alzheimer’s disease, Parkinson’s disease, and more recently SBMA. Another neuropeptide that has a neurotrophic effect on MNs is insulin-like growth factor 1 (IGF-1), also known as somatomedin C. These two peptides are implicated in the activation of neuroprotective pathways exploitable in the amelioration of pathological outcomes related to motor neuron disorders (MNDs).